Usage and Impact of Hotel Mobile Applications on Customer Loyalty: The Mediating Role of Customer Satisfaction Amaal M. I1. , Alaa H. A.2 - et. al., Amaal M. I, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Customer loyalty and customer satisfaction are very importantelements for ahotel to remain in the industry. The use of advanced mobile technology and mobileapplications became essential to achieve customer satisfaction.However, existing literature and previous studies on the impact ofhotel mobile applications have mainly focused on the acceptance of mobile technology.This studyaims atempirically testing the influence of mobile applications usage on customer loyalty, taking into account the attributes of the three variables ofthe study . The researchers used mobile applications as the targeted tools under investigation. To measure and identify the results of these applications, a self-survey tool was adoptedin the form of aquestionnaire. The questionnaire was divided into three sections, each section devoted to measuring one of the study variables, and for measuring the three variables in the study.Furthermore, previous studies were used to ensure the reliability of the measuring tools. The hotel mobile applications usage variable was measured by using 21 sentences that seek to evaluatethedimensions of the six variables (Effectiveness,Efficiency,Learnability, Memorability,Errors,Cognitive load). Inaddition, the study provides decision makers in the hotels business with insight on the effect of mobile applications on their customers’ loyalty and gives them ways to increase the level of customer satisfaction.Moreover, the mediating effect of customer satisfaction isidentified in this study within the context of hotels mobile applications. Therefore, this study recommends improving the process of using mobile phone applications in hotels due to its great impact on increasing customer satisfaction and loyalty.